THE INFLUENCE OF DISCIPLINE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT THE OFFICE OF THE MINISTRY OF RELIGION, TANGERANG SELATAN - Dewi Lestari; Santi Octaviyanti; Riri Oktarini (Yayasan Education and Social Center, 2023)
This study aims to partially and simultaneously determine the effect of discipline and work environment on employee performance at the South Tangerang City Ministry of Religion Office. This study uses quantitative research methods and questionnaires as data collection tools. The sampling method utilized a saturated sampling approach, consisting of sixty-five individuals who worked at the Office of the Ministry of Religion of the City of South Tangerang. The data analysis technique used regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of this study indicate that the variables of discipline and work environment partially affect the performance of employees at the Office of the Ministry of Religion of South Tangerang City. The variables of discipline and work environment impact employee performance at the South Tangerang City Ministry of Religion Office